Application of a differential criterion to the study of the convergence of number series - Slyusarchuk, Lyudmila (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
It is shown that most of the number series that are considered in the collection of problems of G. N. Berman in the course of mathematical analysis can be examined for convergence using the differential criterion V. Yu. Slyusarchuk.